The YouTube formula: Information work and community‐building in a visual era. Issue 1 (1st February 2019) - Thomson, Leslie; Caidi, Nadia; Yoon, Kyong; Forcier, Eric; Kim, Alice N.; Chah, Niel
ABSTRACT: In our increasingly visually oriented world, people's information practices shift and adapt accordingly. In this panel, we bring together an international group of scholars to discuss their insights on information practices related to visual platforms such as YouTube. From the information and communication practices of beauty vloggers garnering international attention to YouTubers specializing in building bridges between cultures, the emergence of the K‐pop fandom on YouTube, and the effects of participatory transmedia on viewers' everyday rituals, the panelists share theoretical, empirical, and methodological insights on emerging and evolving everyday information practices. The audience engagement and panelist presentations will coalesce in the formulation of a research agenda that pertains, broadly, to everyday visual engagement, trust and meaning‐making, and community building at local and translocal levels.